PERAN YAYASAN KUNTUM DALAM PEMBERDAYAAN MASYARAKAT MUSLIMAH DI KAMPUNG WISATA BISNIS TEGALWARU CIAMPEA BOGOR - KURNIA, BELA; SUSANTO, AGUS (Tafáqquh: Jurnal Penelitian Dan Kajian Keislaman, 2021)
Abstract: The study aims to analyze roles of the agents of change in Islamic society development in Kampung Wisata Bisnis Tegalwaru Ciampea Bogor by Yayasan Kuantum. The literary study uses library research model. The study concludes that roles implemented by Yayasan Kuantum Indonesia as the agent of change are as follows: (1) Facilitative role, by actively becoming the subject which socializes ideas about KWBT to Tegalwaru citizens, committing deals of cooperation in stating the benefit share from the visit, and engaging them as parts of the KWBT programs’ participants; (2) Educational roles, by awakening the awareness of Tegalwaru small enterprises to be willing to implement change in their own lives, delivering insights and trainings of entrepreneurship, delivering marketing training by using online medias; (3) Representative roles, by seeking the required resources, legalizing the establishment of programs, setting corporations with various external foundations, developing networks with people outside Tegalwaru, using social media roles, websites, television broadcasts, and YouTube videos for the requirements of publication in KWBT and promoting the products of Tegalwaru small enterprises. (4) technical roles, by gathering internal and external potentials through KWBT programs, moreover, Yayasan Kuantum also conducts management to program implementation, and the financial management inside.